Biomagnification and potential health effects of per- and polyfluoroalkyl substances (PFAS) in a terrestrial food web - Frauke Ecke; Bjørnar Ytrehus; Magnus Evander; Birger Hörnfeldt; Alexandra Leijon; Jonas Malmsten; Aleksandra Skrobonja; Lutz Ahrens (Scientific Reports)
Abstract Per- and polyfluoroalkyl substances (PFAS) are persistent organic pollutants with bioaccumulative, biomagnifying and toxic potential, and largely unknown fate and health effects in terrestrial wildlife. In a contaminated area, we studied PFAS in a terrestrial food web including soil, mushrooms, berries, and wild-living herbivores (bank vole and two ungulate species) and a specialized predator (Tengmalm’s owl). In addition, in voles, we studied potential PFAS-induced liver damage and infection with a zoonotic pathogen. Concentrations of PFAS in vole livers were among the highest reported in terrestrial wildlife. Results suggest biomagnification of PFAS from soil, mushrooms, and berries to bank voles, from mushrooms to ungulates and from voles to the owl. Most vole livers showed diffuse cytoplasmic granulation, ranging from mild to severe, as well as mild and variable hepatocellular hypertrophy. We found high prevalence of Orthohantavirus puumalaense infection in bank voles, highlighting the possibility of PFAS-induced infection susceptibility. Our study supports that terrestrial wildlife magnifies PFAS from the environment and highlights largely unexplored yet worrying effects on wildlife health.